Operational modal analysis method application and seismic performance evaluation for an iconic historical building constructed with different construction materials: Historical Elazig Government Office (Türkiye) - Yetkin, Musa (Elsevier, 2024)
Historical buildings have a very important place for societies in terms of culture. For this reason, it is necessary to protect these buildings and transfer them to future generations. The most important risk for historical buildings is the earthquake natural disaster. In order to prevent the vulnerability of historical buildings under the earthquake effect, it is very important to know/ predict the behavior of these historical buildings to possible earthquakes in advance. The most preferred way to learn this behavior is to perform numerical analyses. With these numerical analyses, finite element (FE) models of historical buildings are created and their behaviors under various loads are determined. The most important problem here is to create the most appropriate FE models that will reflect the existing condition of the historical buildings. This problem is significantly eliminated by the experimental tests, which emerged as a result of developing technology and knowledge. In this study, the historical Elazig Government Office, which has the status of one of the first Government Offices in T & uuml;rkiye and built with the use of different building materials together (adobe + cut stone + rubble stone), will be analyzed. Ambient vibration tests of the historical office will be performed. Then, the FE model of the historical office will be updated in the light of the results obtained from the ambient vibration tests. Nonlinear analyses will be performed for the updated FE model. Acceleration record of February 6, 2023 Kahramanmaras, earthquake will be used in the analyses. As a result of the analyses, the seismic performance of the historical Government Office will be determined by evaluating the displacement, base shear force and stresses.
Keywords: Historical building; Ambient vibration tests; Model updating; Nonlinear analysis; Seismic performance